A method to identify the areas at risk for the introduction of avian influenza virus into poultry flocks through direct contact with wild ducks. Issue 4 (22nd February 2018) - Galletti, G.; Santi, A.; Guberti, V.; Paternoster, G.; Licata, E.; Loli Piccolomini, L.; Procopio, A.; Tamba, M.
Summary: Wild dabbling ducks are the main reservoir for avian influenza (AI) viruses and pose an ongoing threat to commercial poultry flocks. Combining the (i) size of that population, (ii) their flight distances and (iii) their AI prevalence, the density of AI‐infected dabbling ducks (DID) was calculated as a risk factor for the introduction of AI viruses into poultry holdings of Emilia‐Romagna region, Northern Italy. Data on 747 poultry holdings and on 39 AI primary outbreaks notified in Emilia‐Romagna between 2000 and 2017 were used to validate that risk factor. A multivariable Bayesian logistic regression was performed to assess whether DID could be associated with the occurrence of AI primary outbreaks. DID value, being an outdoor flock, hobby poultry trading, species reared, length of cycle and flock size were used as explanatory variables. Being an outdoor poultry flock was significantly associated with a higher risk of AI outbreak occurrence. The probability of DID to be a risk factor for AI virus introduction was estimated to be 90%. A DID cut‐off of 0.23 was identified to define high‐risk areas for AI virus introduction. Using this value, the high‐risk area covers 43% of the region. Seventy‐four per cent of the primary AI outbreaks have occurred in that area, containing 39% of the regional poultry holdings. Poultry holdings located in areas with a high DID value should be included in a risk‐based surveillance programme aimed at AI early detection.